Development of Cad Software for Wheel Chair Design (Journal of Science and Technology, 2016)
Anthropometric data of Nigerian paraplegics was used to design wheel chair for the paraplegics. This was done by developing suitable software using Visual Basic, AutoCAD, Access and Corel- Draw programs. The software developed is capable of designing an ergonomically viable wheelchair for any category of paraplegic using their anthropometric data within 2 minutes.